2017
DOI: 10.1111/tbj.12844
|View full text |Cite
|
Sign up to set email alerts
|

Smoking as a risk factor for wound dehiscence in nipple reconstruction: An analysis of 1683 cases

Abstract: In conclusion, we found smoking to be a risk factor for wound disruption following NAC reconstruction. We hope this study provides further evidence for smoking cessation prior to beginning the reconstructive process. DISCLAIMERACS NSQIP and the hospitals participating in the ACS NSQIP are the source of the data used herein; they have not verified and are not responsible for the statistical validity of the data analysis or the conclusions derived by the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The ideal candidate to NAR procedures has aesthetically pleasant breast mounds with adequately vascularized soft tissues [ 3 ]. Certain risk factors can negatively impact wound healing and make NAR more difficult to achieve, including smoking and RT [ 49 , 50 ], that increase risk for necrosis of the neo-nipple [ 6 , 50 , 51 ]. The chosen BR technique is also relevant when planning NAR.…”
Section: Resultsmentioning
confidence: 99%
“…The ideal candidate to NAR procedures has aesthetically pleasant breast mounds with adequately vascularized soft tissues [ 3 ]. Certain risk factors can negatively impact wound healing and make NAR more difficult to achieve, including smoking and RT [ 49 , 50 ], that increase risk for necrosis of the neo-nipple [ 6 , 50 , 51 ]. The chosen BR technique is also relevant when planning NAR.…”
Section: Resultsmentioning
confidence: 99%
“…Smoking reduces scar quality and has a deleterious effect on the vessels by negatively impacting the vascular system . Diabetes mellitus, which can affect wound healing and blood supply to the peripheral parts, was also investigated …”
Section: Discussionmentioning
confidence: 99%
“…18 Diabetes mellitus, which can affect wound healing and blood supply to the peripheral parts, was also investigated. 6,7 Based on such considerations, correlations between various factors were analyzed. The results showed that having two or more of the risk factors resulted in a statistically significant occurrence of necrosis/ischemia (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations